Convergences in Men's and Women's Life Patterns: Lifetime Work, Lifetime Earnings, and Human Capital Investment - Joyce P. Jacobsen; Melanie Khamis; Mutlu Yuksel (Institute for the Study of Labor (IZA), 2014)
The changes in women and men's work lives have been considerable in recent decades. Yet much of the recent research on gender differences in employment and earnings has been of a more snapshot nature rather than taking a longer comparative look at evolving patterns. In this paper, we use 50 years (1964-2013) of US Census Annual Demographic Files (March Current Population Survey) to track the changing returns to human capital (measured as both educational attainment and potential work experience), estimating comparable earnings equations by gender at each point in time. We consider the effects of sample selection over time for both women and men and show the rising effect of selection for women in recent years. Returns to education diverge for women and men over this period in the selection-adjusted results but converge in the OLS results, while returns to potential experience converge in both sets of results. We also create annual calculations of synthetic lifetime labor force participation, hours, and earnings that indicate convergence by gender in worklife patterns, but less convergence in recent years in lifetime earnings. Thus, while some convergence has indeed occurred, the underlying mechanisms causing convergence differ for women and men, reflecting continued fundamental differences in women's and men's life experiences.
Keywords: J3; J16; J24; N3; 330; gender earnings gap; lifetime work; lifetime earnings; human capital investment